ANALISIS POTENSI MONEY POLITICS PADA PEMILU SERENTAK 2024 DALAM PERSPEKTIF THE FRAUD TRIANGLE THEORY - Kartika, Kadek Bagus Putra; Noak, Piers Andreas; Erviantono, Tedi (Jurnal Nawala Politika, 2023)
The 2024 general elections will again use the mechanism of combining the legislative election period with the election of the President/Vice President for the second time after the 2019 simultaneous elections. However, based on the records and findings of the implementation of the 2019 simultaneous elections, the simultaneous model has shifted in the reality of substance in realizing regular leadership succession, as well as the praxis value in guaranteeing Article 22E paragraph (1) of the 1945 Constitution. The presence of complexity in the form of transactional violations between organizers; election participants; and prominent voters is an empirical instrument that has the potential to occur simultaneously in the implementation of simultaneous elections in 2024. With a research method conducted through a literature study and the perspective of The Fraud Triangle theory by Donald R. Cressey, this research seeks to find the potential for money politics in the 2024 Election which will be held in a simultaneous format by using the reality of the 2019 Election and the events that occurred in the 2024 Election stages as supporting instruments. The findings of this study obtained the presence of the potential for money politics in the 2024 simultaneous elections.   Keywords: Money Politics Potential, Simultaneous Elections 2024